The Role of Organizational Learning Processes in Building Smart Organizations in Higher Education Institutions (A Field Study at Lattakia University): (A Field Study at Lattakia University) (Journal of Hama University, 2026)
The research aims to study the relationship between learning processes (information acquisition, information distribution and interpretation, and organizational memory) and the development of smart organizations at the University of Latakia. The study adopted a descriptive-analytical approach as its general methodology. Data was collected through a questionnaire distributed to a sample of 350 administrative staff, with 317 responses deemed valid for analysis using SPSS. Key findings revealed a high level of organizational learning across its dimensions (information acquisition, distribution and interpretation, and organizational memory) as well as a high level of smart organizations at the university. Results indicated a weak correlation between information acquisition and smart organizations, with information acquisition explaining 34.1% of the changes in smart organizations. However, the relationship was positive, linear, and statistically significant. Additionally, an acceptable correlation was found between (information distribution and interpretation), (organizational memory), and smart organizations, with linear correlation coefficients of (R=0.765) and (R=0.725),respectively Information distribution explained 58.5%, while organizational memory explained 52.4% of the changes in smart organizations, both showing positive, linear, and significant relationships.Finally tests revealed an acceptable correlation between organizational learning and smart organizations (R=0.777),indicating a significant relationship. The coefficient of determination (0.603) showed that organizational learning explains 60.3% of the changes in smart organizations at the University of Latakia.
Keywords: organizational learning, information acquisition, information distribution and interpretation, organizational memory, smart organizations